Exploratory Field Case Study of Microbial and Resistance Genes Dynamics in the Maize Phyllosphere Following Fertigation with Anaerobic Digestate - Fabiani, Camila (2025)
Anaerobic digestate from manure, a byproduct of biogas production, is increasingly used as an organic fertilizer in circular agriculture systems. This study assessed the microbiological impact of maize fertigation with anaerobic digestate, focusing on fecal indicators (Escherichia coli, Salmonella), antibiotic resistance genes (ARGs), and integrons. The trial was conducted in a commercial maize field, where on-site manure-based anaerobic digestate was applied via center-pivot irrigation. Leaf samples were collected two days (2 dai) and four weeks (4 wai) after the last fertigation. E. coli and Salmonella were assessed by culturable methods, while ARGs and integrons were analyzed by qPCR. Results showed that E. coli (3 MPN/g) and Salmonella were detected at 2 dai but were undetectable at 4 wai and in the control condition, suggesting transient contamination. The abundance of tetW was approximately tenfold higher in digestate-treated plants than in the control, while no consistent changes were observed for the other genes. Overall, fertigation with anaerobic digestate appears to pose minimal microbiological impact within the specific conditions of this study, although it may act as a source of specific resistance determinants. Although limited by the use of single treated and control plots, this study offers preliminary insight into microbial and resistance gene dynamics in the phyllosphere, providing a basis for future replicated hypothesis-driven studies.